Pengaruh Indeks Pembangunan Manusia, Pengangguran Dan Upah Minimum Terhadap Kemiskinan Pada Lima Kabupaten Di Provinsi Riau - Setiawan, Rezi; Jahrizal, Jahrizal; Widayatsari, Any (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2025)
Poverty is a problem that must be resolved immediately by the five regencies in Riau Province. The five regencies with the highest number of poor people include Rokan Hulu Regency, Kampar Regency, Rokan Hilir Regency, Pelalawan Regency, and Meranti Islands Regency. The high number of poor people can slow down the development process in the region. The human development index, unemployment, and minimum wage are believed to be the causes of the high number of poor people in the five districts in Riau Province. The purpose of this study was to analyze the effect of the human development index, unemployment, and minimum wage on poverty in five regions in Riau Province. This research is quantitative and uses a panel data regression method. The selected research model is the Common Effect. The results showed that the human development index has a negative and insignificant effect on poverty in five regencies in Riau Province. Unemployment has a negative and insignificant effect on poverty in five regencies in Riau Province. Minimum wage has a negative and insignificant effect on poverty in five regencies in Riau Province.